DIDACTIC PRINCIPLES OF USING INFORMATION AND COMMUNICATION TECHNOLOGIES IN AN ELECTRONIC INFORMATION EDUCATION ENVIRONMENT (American Journal of Interdisciplinary Research and Development, 2024)
This article is devoted to the didactic principles of using information and communication technologies in the e-learning environment and the issues of organizing educational activities based on these principles. feedback on their widespread implementation and effective use is provided.